Flow cytometric analysis identifies changes in S and M phases as novel cell cycle alterations induced by the splicing inhibitor isoginkgetin. - Erin J Vanzyl; Kayleigh R C Rick; Alex B Blackmore; Erin M MacFarlane; Bruce C McKay (PLoS ONE)
The spliceosome is a large ribonucleoprotein complex that catalyzes the removal of introns from RNA polymerase II-transcribed RNAs. Spliceosome assembly occurs in a stepwise manner through specific intermediates referred to as pre-spliceosome complexes E, A, B, B* and C. It has been reported that small molecule inhibitors of the spliceosome that target the SF3B1 protein component of complex A lead to the accumulation of cells in the G1 and G2/M phases of the cell cycle. Here we performed a comprehensive flow cytometry analysis of the effects of isoginkgetin (IGG), a natural compound that interferes with spliceosome assembly at a later step, complex B formation. We found that IGG slowed cell cycle progression in multiple phases of the cell cycle (G1, S and G2) but not M phase. This pattern was somewhat similar to but distinguishable from changes associated with an SF3B1 inhibitor, pladienolide B (PB). Both drugs led to a significant decrease in nascent DNA synthesis in S phase, indicative of an S phase arrest. However, IGG led to a much more prominent S phase arrest than PB while PB exhibited a more pronounced G1 arrest that decreased the proportion of cells in S phase as well. We also found that both drugs led to a comparable decrease in the proportion of cells in M phase. This work indicates that spliceosome inhibitors affect multiple phases of the cell cycle and that some of these effects vary in an agent-specific manner despite the fact that they target splicing at similar stages of spliceosome assembly.